Dual antagonists of α5β1/ αvβ1 integrin for airway hyperresponsiveness - Sundaram, Aparna (Bioorg Med Chem Lett, 2020)
Inhibition of integrin alpha5beta1 emerges as a novel therapeutic option to block transmission of contractile forces during asthma attack. We designed and synthesized novel inhibitors of integrin alpha5beta1 by backbone replacement of known alphavbeta1 integrin inhibitors. These integrin alpha5beta1 inhibitors also retain the nanomolar potency against alphavbeta1 integrin, which shows promise for developing dual integrin alpha5beta1/alphavbeta1 inhibitor. Introduction of hydrophobic adamantane group significantly boosted the potency as well as selectivity over integrin alphavbeta3. We also demonstrated one of the inhibitors (11) reduced airway hyperresponsiveness in Ex vivo mouse tracheal ring assay. Results from this study will help guide further development of integrin alpha5beta1 inhibitors as potential novel asthma therapeutics.